Erratum to: Life habits, hox genes, and affinities of a 311 million-year-old holometabolan larva (vol 15, 208, 2015) - Haug, J. T.; Labandeira, C. C.; Santiago-Blay, J. A.; Haug, C.; Brown, Susan J. (My University, 2017)
Following the publication of this article [1] it has been brought to the attention of the authors and the editors of BMC Evolutionary Biology that the description of the newly described genus and species Srokalarva berthei did not fully meet the criteria of availability as defined by the ICZN (International Code of Zoological Nomenclature). The species description and accompanying ZooBank identification numbers were contained in an additional file and not in the main manuscript as required under the ICZN code. This addendum is to ensure that the ICZN criteria for the availability of new names are satisfied. The following systematics section is identical to that published as part of additional file 1 of this article [1], but is republished here to ensure its full availability. The date of publication of the nomenclatural acts is the date that this addendum has been published.
Citation: Haug, J. T., Labandeira, C. C., Santiago-Blay, J. A., Haug, C., & Brown, S. (2016). Life habits, hox genes, and affinities of a 311 million-year-old holometabolan larva (vol 15, 208, 2015). Bmc Evolutionary Biology, 16, 6. doi:10.1186/s12862-016-0725-x
Keywords: Insects; Ecology; Time; Evolutionary Biology; Genetics & Heredity